If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 5 = -11 Reorder the terms: 5 + 2x = -11 Solving 5 + 2x = -11 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + 2x = -11 + -5 Combine like terms: 5 + -5 = 0 0 + 2x = -11 + -5 2x = -11 + -5 Combine like terms: -11 + -5 = -16 2x = -16 Divide each side by '2'. x = -8 Simplifying x = -8
| -4x-39=2x+45 | | 2z^2-18z-24=0 | | 3z^2+2z=4z^2+4z | | 12(4+n)+5(-2n+9)=18 | | -4x+3x=8x+x | | (7x+3)+(5x+9)=180 | | -6(b-4)=33-3b | | -3n+6-n=-42 | | (4x-1)(x+5)=0 | | -4x+28y=12 | | -5y-13=7-15y | | 2x-17=37 | | -3n-13+2n=-24 | | x^2+2x-298=0 | | 4n+5-6n=-17 | | -6x+37=7 | | 6x+50=8 | | 31-5k=17 | | 9x+62=-10 | | 62=8x+2(-1+4x) | | -5-(15y+-1)=2(7y+-16)-y | | 6-2(m+3)=8 | | y^2+12y+68=0 | | 5+1.5y=.375y+6 | | -4=3m+5 | | 7+2r=7 | | 8x+32=9x+36 | | 3(x+2)=5(2x+1) | | x^2+28x-480=0 | | x^3+3x^2-4x-12= | | 2.7=1.3-2d | | 3(4x-1)=4-2(5-3x) |